(untitled) (Journal of Guidance and Counselling Studies, 2016)
The study examined counsellors ’perception on the causes of divorce and its influence on adolescents ’ Academic performances in Awka educational zone. The study adopted a survey research design and was anchored on Attribution theory. The study used a sample size of 31 counsellors from secondary schools in Awka educational zone, Anambra State. The whole population served as the sample. Data was collected using a structured questionnaire developed by the researchers. The data was analysed using simple mean. The findings showed that sexual problem, psychological immaturity, lack of trust, marital infidelity, among others are major causes of marital divorce while prostitution, low self-esteem, low academic achievement, inability to apply acquired knowledge among others are major impacts of divorce on the academic performance of adolescents. Based on the findings, recommendations were made among which are; Awareness programme should be initiated using Counsellors and other Human Relation professionals stressing on the causes and negative influence of divorce on adolescents ’ academic performance.